2015
DOI: 10.1002/app.42072
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐responsive microgel of a water‐soluble monomer via emulsion polymerization

Abstract: Microgel of a water‐soluble monomer [2‐(N‐morpholino)ethyl methacrylate (MEMA)] was successfully prepared in aqueous media via emulsion polymerization by using a novel water‐soluble block copolymer as stabilizer. Characterization studies confirmed monodisperse spherical morphologies of microgels with a diameter of 280 nm at neutral pH. These microgels exhibited multi‐responsive behavior by responding solution pH, temperature, ionic strength, type of dispersing media, and magnetic particles. It swells well at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…[ 34 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. We suggest several research articles, review articles, and book chapters for detailed information on micro/nanogels synthesis by miniemulsion polymerization [ 34 , 62 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Chemical Design Of Functional Microgelsmentioning
confidence: 99%
“…[ 34 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. We suggest several research articles, review articles, and book chapters for detailed information on micro/nanogels synthesis by miniemulsion polymerization [ 34 , 62 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ].…”
Section: Chemical Design Of Functional Microgelsmentioning
confidence: 99%
“…A variety of microgels including polyacrylic acid (PAA), polyacrylamide (PAAm), PNIPAM, and PHEMA, decorated with different functionalities, have been developed by using miniemulsion process . Readers are suggested to refer several research articles, review articles, and book chapters for detailed information on microgel synthesis by miniemulsion polymerization . This method not only provides the possibility of designing highly charged microgel particles but also the microgels based on hydrophilic monomers can be prepared via inverse miniemulsion method .…”
Section: Methods For Designing Functional Microgelsmentioning
confidence: 99%
“…Moreover, there are polymeric systems responsive to more than three stimuli. Tuncer et al 126 prepared microgels of a water‐soluble monomer 2‐( N ‐morpholino) ethyl methacrylate via emulsion polymerization, which exhibited a multi‐responsive behavior by responding to solution pH, temperature, ionic strength, type of dispersing media, and magnetic field. Cao et al 127 reported the synthesis of a quadruple‐stimuli‐responsive block copolymer sensitive to pH, temperature, light, and reducing agents, as demonstrated by TEM and DLS analysis.…”
Section: Multi‐stimuli‐responsive Polymersmentioning
confidence: 99%